Pertanggungjawaban Tindak Pidana Korupsi dalam Penyelundupan Pakaian Bekas Impor - Budi Ariyanto, Yusril Wira; Haniyah, Haniyah; Handayani, Budi (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The objectives of this research are to examine the abuse of authority by customs officials that qualifies as a criminal act of corruption and the criminal liability of customs officials in the implementation of used clothing imports. The researcher uses the Normative Juridical research method and employs a statutory and conceptual approach, using primary and secondary legal materials obtained from literature studies. The actions of customs officials who have abused their authority by falsifying documents have been regulated in Law No. 20 of 2001 on occupational crimes Article 9, then regulated in Article 416 of the Criminal Code regarding officials or civil servants who falsify books or lists specifically for administrative examination. Members of the public who commit criminal acts of abuse of authority are regulated in Law No. 30 of 2014 on Government Administration (UUAP) which is then regulated in Article 17 of UUAP, but Article 17 of UUAP only states that Government Officials are prohibited from abusing authority.